TEXT-TYPE-BOARD AS A LEARNING MEDIA TO INCREASE JUNIOR HIGH SCHOOL STUDENTS’ INDEPENDENT LEARNING - Victory Cahya Adi (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
This study was intended to see whether a set of text type board for junior high school students can help them to find some basic information about text types in English in a simple way. This learning media also help the students find proper sources of information directly. This study was conducted to answer on a question about how the text type board teaching media affect the junior high school students’ learning process. The writer concern about their independent learning on student’s learning process. The data were gathered from questionnaire and interview. All of the data from Research and Information with interview technique was going to be analyzed. The interview was conducted for two of English teacher in SMP Putra Tama and all of the 7th and 8th grades of SMP Putra Tama. The writer presented the learning media called Text-Types-Board. Then, the writer applied it to7th and 8th grades of SMP Putra Tama for four times. The research was conducted on March 29th, 30th2017 and 5th, 6th April 2017. The students said that the availability of the Text Types Board really helps them solve the problem about English texts by themselves.